Endotoxin adsorbent

An inorganic substrate-based endotoxin adsorbent with cationic groups and controlled pore size effectively removes endotoxins while suppressing protein adsorption, addressing the limitations of existing adsorbents and ensuring suitability for sterilization and aqueous samples.

JP2025054862APending Publication Date: 2025-04-08NAGASE CHEMTEX CORPORATION
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023164054
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

Existing endotoxin adsorbents face challenges in effectively removing endotoxins while suppressing protein adsorption, especially when subjected to high-temperature sterilization or radiation, and they are not efficient in removing endotoxins from aqueous samples containing proteins.

Method used

Development of an endotoxin adsorbent using an inorganic substrate with cationic groups containing nitrogen atoms, where the substrate has no pores or pores with diameters of 40 nm or less, allowing for efficient endotoxin adsorption while minimizing protein adsorption.

Benefits of technology

The adsorbent achieves high endotoxin removal efficiency while effectively suppressing protein adsorption, even under high-temperature sterilization or radiation, and is suitable for use in aqueous samples, making it suitable for medical and food applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025054862000001
    Figure 2025054862000001
  • Figure 2025054862000002
    Figure 2025054862000002
  • Figure 2025054862000003
    Figure 2025054862000003
Patent Text Reader

Abstract

To provide an ET adsorbent whose base material is an inorganic material and which is capable of effectively adsorbing ET while inhibiting adsorption of protein.SOLUTION: An endotoxin adsorbent includes an inorganic base material having a cationic group including nitrogen atom, and has no pore or has a pore whose diameter is 40 nm or less. A material of the inorganic base material is preferably a silica base material. The cationic group including nitrogen atom may be bonded to the inorganic base material with or without a spacer interposed therebetween.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an endotoxin adsorbent and a method for producing an endotoxin-removed material using the same. [Background technology]

[0002] Endotoxin (ET) (hereinafter sometimes referred to as "ET") is one of the toxic substances, specifically, lipopolysaccharide (LPS), which is a component of the outer membrane of gram-negative bacteria. ET is composed of polysaccharide and lipid A, and lipid A mainly contributes to the toxicity. When ET is mixed into an injection solution and taken into the body, it causes fever and shock reaction. For this reason, the Japanese Pharmacopoeia specifies that the ET concentration of an injection solution should be 10-100 pg / ml (0.1-1.0 endotoxin unit (EU) / ml) or less. In addition, for example, in recent years, attempts have been made to separate and purify DNA from genetically modified Escherichia coli and the like and use it as a DNA vaccine, but the DNA obtained in this way still contains ET derived from the bacterial body. Therefore, in order to administer the DNA obtained in this way to a living body as a DNA vaccine, it is necessary to remove the remaining ET. For this reason, there is a strong demand for the development of a method to remove ET from pharmaceuticals. In addition, food must be free of ET, and there is a demand to remove ET from ingredients in processed foods.

[0003] One method for removing ET is known to use various ET adsorbents. For example, Patent Document 1 discloses an ET adsorbent comprising cellulose nanofibers having cationic groups with nitrogen atoms. ET, which is a lipopolysaccharide, has anionic heterosaccharides such as N-acetylgalactosamine and N-acetylglucosamine, and anionic hydrogen phosphate ions. Generally, when an ET adsorbent having a cationic group is used to remove ET from a material containing a substance having a cationic group, competition for ET adsorption occurs between the ET adsorbent and the substance having a cationic group, and ET cannot be sufficiently removed. Nevertheless, the ET adsorbent of Patent Document 1 can sufficiently remove ET from a material containing a substance having a cationic group. However, since the ET adsorbent in Patent Document 1 is made of an organic material, it is easily denatured when subjected to high-temperature sterilization or radiation sterilization, making it difficult to use for removing ET from medical materials that require high-temperature sterilization or radiation sterilization of the adsorbent.

[0004] Patent Document 2 is a document that discloses an ET adsorbent made of an inorganic material. Patent Document 2 describes that an adsorbent in which a silane coupling agent having an amino group is bonded to silica gel adsorbs ET while suppressing the adsorption of amino acids. However, the ET adsorbent of Patent Document 2 cannot sufficiently suppress the adsorption of proteins. Many pharmaceuticals, foods, and cosmetics that contain proteins as target components are commercially available, but since proteins are biologically derived components, there is a risk that ET may be contaminated. Therefore, there is a need to specifically adsorb and remove ET while suppressing the adsorption of target proteins. [Prior art documents] [Patent documents]

[0005] [Patent Document 1] International Publication No. 2017 / 018524 [Patent Document 2] Japanese Patent Publication No. 4-256434 Summary of the Invention [Problem to be solved by the invention]

[0006] An object of the present invention is to provide an ET adsorbent based on an inorganic material, which can effectively adsorb ET while suppressing protein adsorption. [Means for solving the problem]

[0007] In order to solve the above problems, the present inventors conducted extensive research and found that a material that contains an inorganic substrate having a cationic group containing a nitrogen atom and has no pores or has pores with a pore size of 40 nm or less has extremely low protein adsorption and can adsorb ET extremely efficiently.

[0008] The present invention has been completed based on the above findings, and provides the following [1] to [7]. [1] An endotoxin adsorbent comprising an inorganic substrate having a cationic group containing a nitrogen atom, and having no pores or, even if it has pores, the pore size is 40 nm or less. [2] The endotoxin adsorbent according to [1], wherein the inorganic substrate is a silica substrate. [3] The endotoxin adsorbent according to [1] or [2], wherein the cationic group containing a nitrogen atom is bound to the inorganic base material with or without a spacer. [4] The endotoxin adsorbent according to [3], wherein the cationic group containing a nitrogen atom is bound to the inorganic base material via a spacer, and the spacer is a molecular chain having an epoxy group, an isocyanate group, or a hydroxyl group and a functional group capable of reacting with a functional group possessed by the inorganic base material, or a compound which generates these functional groups by ring-opening. [5] The endotoxin adsorbent according to any one of [1] to [4], which is in a particulate form and has an average particle size of 1 to 1000 μm. [6] A column for removing endotoxin, comprising a column packed with the endotoxin adsorbent according to any one of [1] to [5]. [7] A method for producing a liquid containing the protein and from which endotoxin has been removed, comprising the step of contacting a liquid to be treated containing the protein and endotoxin with the endotoxin adsorbent described in any one of [1] to [5]. Effect of the Invention

[0009] The ET adsorbent of the present invention, even if it has pores, has a pore size of 40 nm or less, and therefore has excellent ET adsorption ability while effectively suppressing protein adsorption, and can therefore be suitably used for removing ET from samples containing proteins as target components.

[0010] In order to use the adsorbent for removing ET from medical materials or food materials, it is necessary to sterilize the adsorbent by high temperature, high temperature and high pressure, or radiation. In this regard, the ET adsorbent of the present invention has an inorganic base material and is therefore not easily denatured by high temperature, high temperature and high pressure, or radiation sterilization, and can be suitably used for removing ET from medical materials or food materials.

[0011] Inorganic substrates are generally highly hydrophilic, so that the ET adsorbent of the present invention can efficiently remove ET from aqueous samples, and since liquids containing proteins are generally aqueous, the ET adsorbent of the present invention can be used to remove ET from a wide range of samples containing proteins. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below. (1) Endotoxin adsorbent The endotoxin (ET) adsorbent of the present invention is an ET adsorbent which comprises an inorganic base material having a cationic group containing a nitrogen atom and has no pores, or even if it has pores, the pore size is 40 nm or less.

[0013] Cationic groups containing nitrogen atoms Examples of the cationic group containing a nitrogen atom include an amino group, a quaternary ammonium group, an imino group, an amidine group, a guanidino group, an imidazole group, a quaternary imidazolium group, a pyridyl group, and a quaternary pyridinium group. An amino group is a functional group (primary amino group) (-NH 2), a functional group obtained by removing one hydrogen atom from a primary amine (secondary amino group) (-NHR), or a functional group obtained by removing one hydrogen atom from a secondary amine (tertiary amino group) (-NRR'). Examples of the cationic group containing a nitrogen atom include an aliphatic group, an alicyclic group, an aromatic group, and a heterocyclic group. Among these, an aliphatic group is preferable.

[0014] Method for introducing a cationic group containing a nitrogen atom The ET adsorbent of the present invention can be one in which a cationic group containing a nitrogen atom is bound to an inorganic substrate with or without a spacer (ie, directly).

[0015] When the ET adsorbent of the present invention has a spacer, the cationic group containing a nitrogen atom can be introduced by reacting the inorganic substrate with a crosslinking agent to introduce a reactive functional group into the inorganic substrate, and then reacting it with a donor of a cationic group containing a nitrogen atom. Alternatively, the cationic group can be introduced by first reacting the crosslinking agent with a donor of a cationic group containing a nitrogen atom to obtain a molecular chain having a cationic group, and then reacting this molecular chain with the inorganic substrate. When the crosslinking agent itself has a cationic group containing a nitrogen atom, it may be bonded to the inorganic substrate, and may further be reacted with a donor of a cationic group containing a nitrogen atom.

[0016] As a crosslinking agent that can be used for introducing a spacer, a molecular chain having a functional group such as an epoxy group, an isocyanate group, or a hydroxyl group that can react with a cationic group of a cationic group donor containing a nitrogen atom, and a functional group such as a hydroxyl group present on the surface of an inorganic substrate (for example, a hydroxyl group or a functional group that generates a hydroxyl group by hydrolysis), or a compound that generates such a functional group by ring opening can be used. Examples of such crosslinking agents include polyhydric alcohols, oxazoline compounds, epoxy compounds, silane coupling agents having a functional group that can react with a cationic group having a nitrogen atom, and isocyanate compounds. Polyvalent amines can also be used as crosslinking agents in combination with polyvalent epoxy compounds. One or more types of crosslinking agents can be used.

[0017] Examples of the polyhydric alcohol include ethylene glycol, glycerin, polyglycerin, 1,2-cyclohexanol, pentaerythritol, and sorbitol.

[0018] Examples of polyvalent amines include ethylenediamine, diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, polyethyleneimine, and inorganic or organic salts thereof (eg, azithinium salts).

[0019] The oxazoline compound includes 1,2-ethylenebisoxazoline and the like.

[0020] Examples of epoxy compounds include resorcinol glycidyl ether, hydrogenated bisphenol A diglycidyl ether, phthalic acid diglycidyl ester, ethylene glycol diglycidyl ether, polyethylene glycol diglycidyl ether, glycerol polyglycidyl ether, diglycerol polyglycidyl ether, polyglycerol polyglycidyl ether, propylene glycol diglycidyl ether, and polypropylene glycol diglycidyl ether.

[0021] Examples of the silane coupling agent include polyfunctional silane coupling agents such as 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 3-glycidoxypropylmethyldiethoxysilane, 3-glycidoxypropylmethyldimethoxysilane, 3-glycidoxypropyltriethoxysilane, 3-glycidoxypropyltrimethoxysilane, p-styryltrimethoxysilane, 3-trimethoxysilylpropylsuccinic anhydride, 3-triethoxysilylpropylsuccinic anhydride, tris-(trimethoxysilylpropyl)isocyanurate, 3-isocyanatepropyltriethoxysilane, and dithioltriazinepropyltriethoxysilane. Further examples include silane oligomers obtained by oligomerizing each silane coupling agent.

[0022] Examples of the isocyanate compound include hexamethylene diisocyanate, m-xylene diisocyanate, toluene-2,4-diisocyanate, naphthalene diisocyanate, 4,4'-diphenylmethane diisocyanate, isophorone diisocyanate, and 1,4-phenylene diisocyanate.

[0023] Among these crosslinking agents, silane coupling agents and isocyanate compounds are preferred, and among them, silane coupling agents having an epoxy group are preferred, with 3-glycidoxypropyltriethoxysilane and 3-glycidoxypropylmethyldiethoxysilane being more preferred.

[0024] Examples of the crosslinking agent having a cationic group containing a nitrogen atom include silane coupling agents having a cationic group containing a nitrogen atom, such as [3-(diethylamino)propyl]trimethoxysilane, N-2-(aminoethyl)-3-aminopropylmethyldimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-triethoxysilyl-N-(1,3-dimethyl-butylidene)propylamine, N-phenyl-3-aminopropyltrimethoxysilane, and 3-ureidopropyltrialkoxysilane. Among these, [3-(diethylamino)propyl]trimethoxysilane, [3-(diethylamino)propyl]triethoxysilane, N-[3-(trimethoxysilyl)propyl]butan-1-amine, 3-aminopropyltriethoxysilane, and 3-(methylamino)propyltriethoxysilane are preferred.

[0025] Examples of the nitrogen atom-containing cationic compound, which is a donor of a nitrogen atom-containing cationic group, include ammonia, amidine, amine (primary amine, secondary amine, tertiary amine), quaternary ammonium salt, quaternary imidazolium salt, and quaternary pyridinium salt. As described above, when the crosslinking agent contains a cationic group containing a nitrogen atom, the crosslinking agent can serve as a donor of the cationic group containing a nitrogen atom.

[0026] In the ET adsorbent of the present invention, the cationic group containing a nitrogen atom is a cationic group derived from a cationic group donor containing a nitrogen atom, that is, a cationic group derived from a cationic compound containing a nitrogen atom. The donor of the cationic group containing a nitrogen atom may contain one cationic group containing a nitrogen atom, or may contain two or more cationic groups containing a nitrogen atom. For example, when the cationic compound containing a nitrogen atom is an amine, it may be any of a monovalent amine, a divalent amine or a polyvalent amine having two or more amines. The cationic compounds containing nitrogen atoms can be either polymeric or non-polymeric.

[0027] The monovalent amines include aliphatic amines, particularly alkylamines (primary amines such as methylamine, ethylamine, propylamine, butylamine, pentylamine, hexylamine, heptylamine, coconut amine, octylamine, nonylamine, decylamine, laurylamine, stearylamine, and oleylamine; secondary amines such as dimethylamine, diethylamine, dipropylamine, dibutylamine, dipentylamine, dihexylamine, diheptylamine, dioctylamine, dinonylamine, and didecylamine; Secondary amines; trimethylamine, triethylamine, tripropylamine, tributylamine, diisopropylethylamine, N,N-dimethylethylamine, N,N-dimethylpropylamine, N,N-dimethylbutylamine, N,N-dimethylpentylamine, N,N-dimethylhexylamine, N,N-dimethylheptylamine, N,N-dimethyloctylamine, N,N-dimethylnonylamine, N,N-dimethylcoconutamine, N,N-dimethyldecylamine, N,N-dimethyllaurylamine, N,N-dimethylmine Tertiary amines such as listrylamine, N,N-dimethylpalmitylamine, N,N-dimethylstearylamine, dimethylbehenylamine, didecylmonomethylamine, and trioctylamine; aromatic amines (primary amines such as aniline and toluidine); heterocyclic amines (secondary amines such as pyrrolidine, piperidine, morpholine, and imidazole; tertiary amines such as pyridine, 2,4,6-trimethylpyridine (collidine), 2,6-lutidine, quinoline, N-methylmorpholine, and N-ethylmorpholine). alkanolamines or aminoalcohols (primary amines such as monomethanolamine, monoethanolamine, monoisopropanolamine, 2-amino-2-methyl-1-propanol, 2-amino-2-methyl-1,3-propanediol, 3-amino-1,2-propanediol, 3-dimethylamino-1,2-propanediol, tris(hydroxymethylamino)methane; secondary amines such as diethanolamine, diisopropanolamine, N-methylethanolamine, N-ethylethanolamine;Tertiary amines such as triethanolamine, triisopropanolamine, N-dimethylaminoethanol, and N-diethylaminoethanol;

[0028] Polyamines include aliphatic diamines such as ethylenediamine, tetramethylethylenediamine, tetramethylenediamine, and hexamethylenediamine; 4,4'-diamino-3,3'-dimethyldicyclohexylmethane, 3-(diethylamino)propylamine, and 3-(dimethylamino)propylamine. Alicyclic diamines such as 1-propylamine, N,N,N',N'-tetramethyl-1,6-diaminohexane, diaminecyclohexane, and isophoronediamine; aromatic diamines such as phenylenediamine, diaminonaphthalene, and xylylenediamine; heterocyclic diamines such as piperazine and 1,4-bis(3-aminopropyl)piperazine; aliphatic amines having a valence of 3 or more such as diethylenetriamine, triethylenetetramine, tetraethylenepentamine, pentaethylenehexamine, hexaethylenepentamine, N,N'-dimethyldipropylenetriamine, tris(2-aminoethyl)amine, tris(3-aminopropyl)amine, and guanidine; and aromatic amines having a valence of 3 or more such as melamine. In addition, examples of polyvalent amines include polymers having amino groups such as polyethyleneimine, polyvinylamine, polyallylamine, methoxypoly(oxyethylene / oxypropylene)-2-propylamine, polyoxypropylenediamine, polyetheramine, triethyleneglycoldiamine, trimethylolpropanepoly(oxypropylene)triamine, glycerylpoly(oxypropylene)triamine, amino acids (especially basic amino acids such as lysine, arginine, histidine, ornithine, and tryptophan), amino acid polymers (especially basic amino acid polymers such as polylysine, polyarginine, polyhistidine, polyornithine, and polytryptophan), and polycreatinine.The polymer may be either linear or branched.

[0029] Examples of quaternary ammonium salts include glycidyltrimethylammonium salts (hydrochloride, hydrobromide, etc.), etc. In addition, for example, quaternary amines obtained by alkylating the above-listed tertiary amines can also be used. Examples of quaternary imidazolium salts include 1-decyl-3-methylimidazolium salts, 1-methyl-3-octylimidazolium salts, and 1-methyl-benzimidazolium salts (such as hydrochloride and hydrobromide salts). Examples of the quaternary pyridinium salt include butylpyridinium salt, dodecylpyridinium salt (hydrochloride, hydrobromide, etc.), and the like.

[0030] The nitrogen atom-containing cationic compound is preferably an aliphatic amine. The nitrogen atom-containing cationic compound may be used alone or in combination of two or more kinds. When two or more types of cationic compounds are used, inorganic base materials into which respective cationic groups have been introduced may be mixed and used, or inorganic base materials into which two or more types of cationic groups have been introduced may be used.

[0031] In addition, after the cationic group containing a nitrogen atom is introduced into the inorganic base material, the cationic property can be enhanced by further modifying the base material. For example, cationicity can be increased by quaternizing the amino group. Examples of compounds for quaternizing the amino group include epoxy group donors such as chloromethyloxirane (epichlorohydrin), glycidyl methacrylate, glycidyl acrylate, diglycidyl ether, epibromohydrin, and ethylene glycol diglycidyl ether, p-toluenesulfonic acid chloride, 2-fluoro-1-methylpyridinium, chloroacetyl chloride, hexamethylene diisocyanate, m-xylene diisocyanate, toluene-2,4-diisocyanate, iodomethane, and iodoethane. Cationicity can also be increased by additionally introducing a cationic group containing a nitrogen atom. A method for additionally introducing a cationic group containing a nitrogen atom includes activating the introduced cationic group with an activator (e.g., a compound that quaternizes an amino group) and then reacting it with a cationic compound containing a nitrogen atom, which is the same as or different from the cationic group already introduced. The cationic compound containing a nitrogen atom can be one exemplified above. The compound to be reacted to enhance cationicity may be used alone or in combination of two or more kinds.

[0032] The reaction conditions between the inorganic substrate and the crosslinking agent can be appropriately determined by a person skilled in the art depending on the crosslinking agent used, whether the cationic group having a nitrogen atom is introduced into the crosslinking agent in advance or the cationic group having a nitrogen atom is introduced after the inorganic substrate is reacted with the crosslinking agent. This reaction may be carried out, for example, at about 10 to 100°C for about 0.1 to 48 hours. If necessary, a suitable catalyst and solvent may be used. As the solvent, water is usually used, but aprotic polar solvents such as alcohols such as methanol, ethanol, 2-propanol, and ethylene glycol monomethyl ether (2-methoxyethanol), dimethylformamide, and dimethylsulfoxide may also be used.

[0033] Inorganic base material Examples of inorganic substrate materials include silica (silica gel, silica monolith, etc.), alumina, aluminum hydroxide, titanium oxide, talc, diatomaceous earth, perlite, zeolite, vermiculite, kaolinite, sepiolite, mineral shirasu, shirasu porous glass, etc. Among these, silica is preferred, silica without a monolith structure is more preferred, and silica gel is even more preferred. The inorganic materials can be used alone or in combination (particularly as a mixture) of two or more kinds.

[0034] Characteristics of ET adsorbent The ET adsorbent of the present invention may be pore-free or porous. When the adsorbent is porous, the average pore size is 40 nm or less. Preferably, the average pore size is 35 nm or less, 30 nm or less, 25 nm or less, 24 nm or less, or 23 nm or less. The average pore size may be 1 nm or more, 2 nm or more, or 3 nm or more. Within this range, the adsorption of protein can be suppressed while adsorbing ET. In the present invention, the average pore size is a value measured by a gas adsorption method and calculated by the Barrett-Joyner-Halenda method (BJH method). Specifically, it is a value measured by the method described in the Examples. The average pore diameter is the average pore diameter of the inorganic substrate to which the nitrogen-containing cationic group is bonded.

[0035] When the ET adsorbent of the present invention is porous, the specific surface area is 0.1 m 2 / g or more, 1m 2 / g or more, 10m 2 / g or more, or 100m 2 / g or more. In this range, ET can be efficiently adsorbed. 2 / g or less, 1000m 2 / g or less, 900m 2 / g or less, or 800m 2 / g or less. In the present invention, the specific surface area is a value measured by the BET (Brunauer-Emmett-Teller) method.

[0036] The ET adsorbent of the present invention may or may not have through-holes with an average pore size of the order of μm. The through-holes are a porous structure that communicates with the inside of the ET adsorbent, and the ends of the through-holes are holes that open toward the outside of the ET adsorbent. It is preferable that the ET adsorbent of the present invention does not have such through-holes.

[0037] The ET adsorbent of the present invention may be in any shape, such as particulate, crushed, fibrous, membrane, hollow fiber, nonwoven fabric, columnar, etc. A cationic group having a nitrogen atom may be introduced into a substrate of such shape, but for example, a cationic group having a nitrogen atom may be introduced into a particulate or fibrous substrate, which may then be processed into a membrane, columnar, or other shape.

[0038] When the ET adsorbent of the present invention is in a particulate or crushed form, the average particle size can be 1 μm or more, 10 μm or more, 20 μm or more, 40 μm or more, more than 40 μm, 60 μm or more, 80 μm, or 100 μm or more, and can be 1000 μm or less, 700 μm or less, 500 μm or less, 400 μm or less, or 300 μm or less. Within this range, ET can be efficiently removed while suppressing protein adsorption, and the adsorbent can be easily separated from the aqueous liquid from which ET is removed. In the present invention, the average particle size is a value measured by a sieving method.

[0039] When the ET adsorbent of the present invention is in a particulate or crushed form, the particle size of the particle aggregate is preferably within the range of 40 to 600 μm, particularly 40 to 300 μm, particularly 40 to 200 μm, particularly 75 to 150 μm. Within this range, ET can be efficiently removed while suppressing protein adsorption, and the ET can be easily separated from the aqueous liquid from which ET is removed. In the present invention, the particle size is a value measured by a sieving method. For example, when the particle size is 75 to 150 μm, it is a particle aggregate that passes through a sieve with a mesh size of 150 μm but does not pass through a sieve with a mesh size of 75 μm.

[0040] The content of amino groups in the ET adsorbent of the present invention can be 0.01 meq / dry·g or more, 0.05 meq / dry·g or more, 0.1 meq / dry·g or more, 0.2 meq / dry·g or more, or 0.5 meq / dry·g or more in terms of anion exchange capacity (AEC). Within this range, ET can be sufficiently adsorbed and removed. In addition, it can be 20 meq / dry·g or less, 10 meq / dry·g or less, 5 meq / dry·g or less, or 1 meq / dry·g or less. Within this range, ET can be efficiently removed while suppressing protein adsorption. In the present invention, the ion exchange capacity is a value measured by a pH titration method.

[0041] The ET adsorption rate of the ET adsorbent of the present invention can be more than 98%, particularly 99% or more, when 10% by weight of the test ET adsorbent is used in an aqueous solution containing 315 EU / g ET and 1% by weight of γ-globulin and stirred at room temperature for 1 hour in a batch method. The upper limit of the ET adsorption rate can be 100%. In addition, the ET adsorption rate per AEC of the ET adsorbent of the present invention may be, for example, 50%·dry weight / mEq or more, 100%·dry weight / mEq or more, or 150%·dry weight / mEq or more, or 1000%·dry weight / mEq or less, or 500%·dry weight / mEq or less, when, for example, 30% by weight of the test ET adsorbent is used in an aqueous solution containing 315 EU / g ET and 1% by weight of γ-globulin and stirred at room temperature for 1 hour in a batch method.

[0042] The protein adsorption rate of the ET adsorbent of the present invention may be 8% or less, preferably 7% or less, preferably 6% or less, preferably 5% or less, when 10% by weight of the test ET adsorbent is used in an aqueous solution containing 315 EU / g ET and 1% by weight of γ-globulin and stirred at room temperature for 1 hour in a batch process. The lower limit of the protein adsorption rate may be 0%.

[0043] ET adsorbent A material having an inorganic substrate having a cationic group containing a nitrogen atom and having no pores or having pores with a pore size of 40 nm or less can be used as the ET adsorbent of the present invention, either alone or in combination with other components. The ET adsorbent of the present invention can be used as a material for adsorbing ET while suppressing the adsorption of proteins. The ET adsorbent of the present invention can be packed in a column for use. A column packed with the ET adsorbent of the present invention can be used as an ET removal column. This column can be used as a column for removing ET while suppressing protein adsorption.

[0044] (2) ET removal method The liquid to be treated with the ET adsorbent of the present invention is a liquid containing protein and ET. By contacting the liquid to be treated with the ET adsorbent of the present invention, ET in the liquid to be treated is adsorbed to the ET adsorbent, and adsorption of proteins is suppressed. For example, proteins are hardly or not adsorbed at all. This makes it possible to remove ET from the liquid containing proteins. Then, the liquid from which ET has been removed can be separated from the ET adsorbent to which ET has been adsorbed. That is, the ET removal method of the present invention is a method comprising a step of contacting the ET adsorbent of the present invention with a liquid to be treated. In addition, the method may further comprise a step of separating the liquid from which ET has been removed from the ET adsorbent having adsorbed ET, for example, a step of recovering the liquid from which ET has been removed from a mixture of the ET adsorbent of the present invention and the liquid to be treated. In other words, the ET removal method of the present invention is a method for producing a liquid from which ET has been removed. The ET removal method of the present invention may also be a method for producing a liquid containing a protein from which ET has been removed, or a method for purifying a protein.

[0045] The liquid to be treated may be any liquid having flowability, including viscous liquids, and may also be a material that becomes flowable when heated or warmed. The liquid to be treated may contain one type of target component, or may contain two or more types of target components. The target component is a necessary component contained in the liquid to be treated and should not be removed. At least one or more types of target components may be proteins. The proteins may have a protein portion, and include simple proteins, as well as glycoproteins, lipoproteins, metalloproteins, hemoproteins, phosphoproteins, and the like. Among these, proteins and glycoproteins are preferred. The ET and the target component in the liquid to be treated may be dissolved or suspended in the liquid. Even when the ET adsorbent of the present invention is brought into contact with an aqueous composition, it is easy to separate from the aqueous composition after contact, so that the liquid to be treated is preferably a material containing water.

[0046] The liquid to be treated is preferably a solution or suspension containing a protein, which may be a pharmaceutical product, a quasi-drug, a cosmetic, a food product, or the like.

[0047] The ET adsorbent of the present invention can be contacted with the liquid to be treated, for example, by a batch method. The "batch method" is a method in which the ET adsorbent of the present invention is contacted with the liquid to be treated by mixing them in a suitable container. The batch method may be performed by leaving the adsorbent at rest, or by stirring or shaking. The contact time varies depending on the type of the liquid to be treated, and can be, for example, 5 minutes to 120 hours, 30 minutes to 24 hours, 1 to 12 hours, or 2 to 4 hours. The temperature during contact varies depending on the type of the liquid to be treated, and can be, for example, 5 to 80°C, 15 to 65°C, or 25 to 50°C. After ET is adsorbed to the ET adsorbent of the present invention, the ET adsorbent of the present invention can be separated from the mixture by filtration, centrifugation, or the like.

[0048] The ET adsorbent of the present invention can be contacted with the liquid to be treated by, for example, a flow separation method. The "flow separation method" is a method in which the ET adsorbent of the present invention is contacted with the liquid to be treated by passing the liquid to be treated through the ET adsorbent of the present invention. Specifically, for example, the ET adsorbent of the present invention can be packed in a column and the liquid to be treated is passed through the column to bring the ET adsorbent of the present invention into contact with the liquid to be treated. For example, when the ET adsorbent of the present invention is formed into a filter shape, the ET adsorbent of the present invention can be contacted with the liquid to be treated by passing the liquid to be treated through the filter. Examples of the membrane include a membrane filter, a hollow fiber membrane, and a tubular membrane. When the ET adsorbent of the present invention is formed into a column shape, the ET adsorbent of the present invention can be contacted with the liquid to be treated by passing the liquid to be treated through the column. The ET adsorbent of the present invention can be contacted with the liquid to be treated by placing the ET adsorbent of the present invention on a filter paper and passing the liquid to be treated through it.

[0049] The ET removal method of the present invention removes ET from a liquid to be treated. The degree of ET removal may be such that the ET concentration or content of the liquid to be treated after treatment (after contact with the ET adsorbent of the present invention) is lower than that before treatment (before contact with the ET adsorbent of the present invention). "ET is removed" may mean, for example, that the ET concentration or content in the liquid obtained by treating the liquid to be treated with the ET adsorbent is reduced to 50% or less, 30% or less, 20% or less, 10% or less, 5% or less, 2% or less, less than 2%, or 1% or less compared to before treatment. That is, the ET removal rate may be 50% or more, 70% or more, 80% or more, 90% or more, 95% or more, 98% or more, more than 98%, or 99% or more. The ET quantification method includes the Limulus test using a Limulus reagent. The Limulus test can be performed by a conventional method. For example, the Limulus test can be performed by a colorimetric method, a turbidimetric method, a gelation method, or the like.

[0050] "Proteins in the liquid to be treated are not removed" may mean that the protein content in the liquid to be treated after treating the liquid to be treated is maintained at 90% or more, 92% or more, 95% or more, 97% or more, 98% or more, or 99% or more compared to before treatment. Proteins can be quantified by ultraviolet absorption method, Bradford method (Coomassie Blue method), Lowry method (phenol reagent method), bicinchoninic acid method (BCA method), or the like. EXAMPLES

[0051] The present invention will be described in more detail below by way of examples, but the present invention is not limited to these. (1) Preparation of cationized silica gel particles Example 1 In a separable flask, 1.4 g of a silane coupling agent, [3-(diethylamino)propyl]trimethoxysilane (trade name "D4362"; Tokyo Kasei Co., Ltd.), 50 g of denatured alcohol (trade name "AP-7"; Japan Alcohol Sales Co., Ltd.), and 50 g of water were placed. Next, 5 g of granular silica gel (CARiACT Q-3; Fuji Silysia Chemical Co., Ltd.) was added. The mixture was further stirred at room temperature for 24 hours. The obtained slurry was suction filtered on a filter cloth (trade name "TF-301B"; Toray Industries, Inc.), rinsed with a large amount of denatured alcohol, and then rinsed with a large amount of water to obtain [3-(diethylamino)propyl]trimethoxysilane (DEAP)-immobilized silica gel particles. The average pore size of the obtained particles was 4 nm, and the particle size was 75 to 150 μm.

[0052] Example 2 Except for using granular silica gel (CARiACT Q-6; Fuji Silysia Chemical) as the base material, DEAP-immobilized silica gel particles were obtained in the same manner as in Example 1. The average pore size of the obtained particles was 7 nm, and the particle size was 75 to 150 μm.

[0053] Example 3 Except for using granular silica gel (CARiACT Q-10; Fuji Silysia Chemical) as the base material, DEAP-immobilized silica gel particles were obtained in the same manner as in Example 1. The average pore size of the obtained particles was 16 nm, and the particle size was 75 to 150 μm.

[0054] Example 4 Except for using granular silica gel (CARiACT Q-14; Fuji Silysia Chemical) as the base material, DEAP-immobilized silica gel particles were obtained in the same manner as in Example 1. The average pore size of the obtained particles was 23 nm, and the particle size was 75 to 150 μm.

[0055] Example 5 In a separable flask, 4 g of a silane coupling agent, 3-glycidoxypropylmethyldiethoxysilane (trade name "KBE-402"; Shin-Etsu Chemical Co., Ltd.), was placed, and 25 g of 0.05% acetic acid was added, followed by stirring at room temperature for 1 hour. Next, 5 g of granular silica gel (CARiACT Q-3; Fuji Silysia Chemical Co., Ltd.) was added. The mixture was further stirred at 45°C for 24 hours. The resulting slurry was suction filtered on a filter cloth (trade name "TF-301B"; Toray Industries, Inc.) and rinsed with a large amount of water to obtain epoxy group-introduced granular silica gel particles (hereinafter also referred to as "EP-PSM"). The obtained EP-PSM was dispersed in 60 g of denatured alcohol (trade name "AP-7"; Japan Alcohol Sales Co., Ltd.) and 60 g of water. Next, 32 g of N,N-dimethyldecylamine (trade name "D2288"; Tokyo Chemical Industry Co., Ltd.) (DDA) was added, and the mixture was stirred in a 45°C water bath for 24 hours. The reaction product was suction filtered on a filter cloth, rinsed with a large amount of denatured alcohol, and then rinsed with a large amount of water to obtain N,N-dimethyldecylamine (DDA)-immobilized silica gel particles. The average pore size of the obtained particles was 4 nm, and the particle size was 75 to 150 μm.

[0056] Example 6 Similarly to Example 5, DMOA-immobilized silica gel particles were obtained in the same manner as in Example 5, except that N,N-dimethyloctylamine (product name "D1814"; Tokyo Chemical Industry Co., Ltd.) (DMOA) was used instead of DDA as the cationic group-donor compound.

[0057] Example 7 As in Example 1, TMPB-immobilized silica gel particles were obtained in the same manner as in Example 1, except that N-[3-(trimethoxysilyl)propyl]butan-1-amine (product name "T3733"; Tokyo Chemical Industry Co., Ltd.) (TMPB) was used instead of the silane coupling agent DEAP.

[0058] Example 8 AP-immobilized silica gel particles were obtained in the same manner as in Example 1, except that 3-aminopropyltriethoxysilane (product name "A0439"; Tokyo Chemical Industry Co., Ltd.) (AP) was used instead of the silane coupling agent DEAP.

[0059] Example 9 As in Example 1, MAP-immobilized silica gel particles were obtained in the same manner as in Example 1, except that 3-(methylamino)propyltriethoxysilane (product name "T1255"; Tokyo Chemical Industry Co., Ltd.) (MAP) was used instead of the silane coupling agent DEAP.

[0060] Example 10 In a separable flask, 1.4 g of a silane coupling agent, [3-(diethylamino)propyl]trimethoxysilane (trade name "D4362"; Tokyo Kasei Co., Ltd.), 50 g of denatured alcohol (trade name "AP-7"; Japan Alcohol Sales Co., Ltd.), and 50 g of water were placed. Next, 5 g of granular silica gel (Sunsphere D200L; AGC Si-Tech Co., Ltd.) was added. The mixture was further stirred at room temperature for 24 hours. The obtained slurry was suction filtered on a filter cloth (trade name "TF-301B"; Toray Industries, Inc.), rinsed with a large amount of denatured alcohol, and then rinsed with a large amount of water to obtain [3-(diethylamino)propyl]trimethoxysilane (DEAP)-immobilized silica gel particles. The average pore size of the obtained particles was 23 nm, and the particle size was 100 to 200 μm.

[0061] Example 11 In a separable flask, 1.4 g of a silane coupling agent, [3-(diethylamino)propyl]trimethoxysilane (trade name "D4362"; Tokyo Kasei Co., Ltd.), 50 g of denatured alcohol (trade name "AP-7"; Japan Alcohol Sales Co., Ltd.), and 50 g of water were placed. Next, 5 g of granular silica gel (Sunsphere D300L; AGC Si-Tech Co., Ltd.) was added. The mixture was further stirred at room temperature for 24 hours. The obtained slurry was suction filtered on a filter cloth (trade name "TF-301B"; Toray Industries, Inc.), rinsed with a large amount of denatured alcohol, and then rinsed with a large amount of water to obtain [3-(diethylamino)propyl]trimethoxysilane (DEAP)-immobilized silica gel particles. The average pore size of the obtained particles was 23 nm, and the particle size was 200 to 300 μm.

[0062] Example 12 In a separable flask, 1.4 g of 3-trimethoxysilylpropylsuccinic anhydride (trade name "T3360"; Tokyo Chemical Industry Co., Ltd.), which is a silane coupling agent, 1 g of N,N-dimethyldecylamine (trade name "D2288"; Tokyo Chemical Industry Co., Ltd.), 50 g of denatured alcohol (trade name "AP-7"; Japan Alcohol Sales Co., Ltd.), and 50 g of water were placed. Next, 5 g of granular silica gel (CARiACT Q-3; Fuji Silysia Chemical Co., Ltd.) was added. The mixture was further stirred at room temperature for 24 hours. The obtained slurry was suction filtered on a filter cloth (trade name "TF-301B"; Toray Industries, Inc.), rinsed with a large amount of denatured alcohol, and then rinsed with a large amount of water to obtain N,N-dimethyldecylamine (DDA)-immobilized silica gel particles. The obtained particles had an average pore size of 4 nm and a particle size of 75 to 150 μm.

[0063] Example 13 In a separable flask, 1.4 g of a silane coupling agent, [3-(diethylamino)propyl]trimethoxysilane (trade name "D4362"; Tokyo Kasei Co., Ltd.), 50 g of denatured alcohol (trade name "AP-7"; Japan Alcohol Sales Co., Ltd.), and 50 g of water were added. Then, 5 g of crushed silica gel (Wakogel 60N; Fujifilm Wako Pure Chemical Industries, Ltd.) was added. The mixture was further stirred at room temperature for 24 hours. The obtained slurry was suction filtered on a filter cloth (trade name "TF-301B"; Toray Industries, Inc.), rinsed with a large amount of denatured alcohol, and then rinsed with a large amount of water to obtain [3-(diethylamino)propyl]trimethoxysilane (DEAP)-immobilized silica gel particles. The average pore size of the obtained particles was 6 nm, and the particle size was 150 to 425 μm.

[0064] Comparative Example 1 Except for using granular silica gel (CARiACT Q-30; Fuji Silysia Chemical) as the base material, DEAP-immobilized silica gel particles were obtained in the same manner as in Example 1. The average pore size of the obtained particles was 43 nm, and the particle size was 75 to 150 μm.

[0065] Comparative Example 2 Except for using granular silica gel (CARiACT Q-50; Fuji Silysia Chemical) as the base material, DEAP-immobilized silica gel particles were obtained in the same manner as in Example 1. The average pore size of the obtained particles was 78 nm, and the particle size was 75 to 150 μm.

[0066] Comparative Example 3 Except for using granular silica gel (SMB-500 / 20 / 45; Fuji Silysia Chemical) as the base material, DEAP-immobilized silica gel particles were obtained in the same manner as in Example 1. The average pore size of the obtained particles was 78 nm, and the particle size was 25 to 32 μm. Comparative Example 4 Granular activated carbon (FP-6 Special Shirasagi; Osaka Gas Chemicals) was used as the adsorbent in Comparative Example 4. No cationic groups were bonded to the granular activated carbon. The average pore size of this granular activated carbon was 3 nm.

[0067] (2) Physical property evaluation (2-1) Anion exchange capacity The anion exchange capacity (AEC) of the cationized silica gel particles of Examples 1 to 13 and Comparative Examples 1 to 3 and the activated carbon particles of Comparative Example 4 was measured by a back titration method using hydrochloric acid. The procedure is as follows. Each particle was dried under reduced pressure at room temperature for 24 hours or more, and 0.5 g was precisely weighed into a screw tube. 20 ml of 0.1 mol / l hydrochloric acid with a known factor was added and stirred on a roller for 2 hours. The particles were filtered using filter paper, and 10 ml of the filtrate was taken into another screw tube. Titration was performed with a 0.05 mol / l aqueous sodium hydroxide solution with a known factor using phenolphthalein as an indicator. The AEC was calculated according to the following formula: AEC (mEq / dry g) = (0.1 × fHCl × 20 - 0.05 × fNaOH × V × 20 / 10) ÷ W fHCl: factor of hydrochloric acid used fNaOH: factor of sodium hydroxide used V: Titration volume (ml) W: Dry weight of the particle (dry g)

[0068] (2-2)ET adsorption capacity The ET adsorption capacity was measured for the cationized silica gel particles of Examples 1 to 13 and Comparative Examples 1 to 3, and the activated carbon particles of Comparative Example 4. The ET adsorption capacity was evaluated by a batch method. The equipment used (conical beaker, whole pipette, pipette, glass filter, medicine spoon, Limulus tube, tube cap) that could be sterilized by dry heat were thoroughly washed and then sterilized at 250°C for 4 hours. The syringes, membrane filters, and tips used had been sterilized by gamma irradiation in advance. Each particle was washed five times with 25 ml of 0.2 M NaOH / 95% EtOH on a glass filter, and then repeatedly washed with sterilized pure water until the filtrate became neutral.

[0069] 0.3 g of the washed adsorbent was weighed into a 10 mL Erlenmeyer flask, and 1 mL of a 1 wt % γ-globulin (derived from human plasma) solution obtained by dissolving γ-globulin (derived from human plasma; Fuji Film Wako Pure Chemical Industries, Ltd.) in water for injection (Otsuka Distilled Water; Otsuka Pharmaceutical Factory, Inc.) or 0.1 mol / L phosphate buffer solution (Fuji Film Wako Pure Chemical Industries, Ltd.) was added, and the flask was shaken at 20°C and 200 rpm for 1 hour in a bioshaker. Next, the aqueous solution containing the adsorbent particles was sucked up with a syringe and filtered through a 0.8 μm membrane filter. The filtrate was diluted 10 to 1000 times with water for injection (Otsuka distilled water). 0.2 ml of the diluted solution was added to test tubes containing the Limulus reagent Endospecy ES-24M (Seikagaku Corporation) and mixed well with a vortex mixer. The test tubes were placed in an EG reader (SV-12; Seikagaku Corporation), and the remaining ET concentration was determined by the colorimetric time method (Ee). In addition, the ET concentration (Es) contained in the γ-globulin (human plasma-derived) solution before contact with the adsorbent was determined by filtering the γ-globulin (human plasma-derived) solution through a 0.8 μm membrane filter, diluting it 10 to 1000 times with water for injection (Otsuka distilled water), and using the Limulus reagent described above by the colorimetric time method, in the same manner as described above. The ET adsorption rate was calculated according to the following formula. ET adsorption rate (%)=[(Es-Ee) / Es]×100

[0070] (2-3) γ-globulin (derived from human plasma) adsorption capacity The adsorption rate of γ-globulin for the cationized silica gel particles of Examples 1 to 13 and Comparative Examples 1 to 3 was measured by the following method. 0.1 g of the washed adsorbent was weighed into a 10 mL Erlenmeyer flask, and 1 mL of a 0.1 wt % γ-globulin aqueous solution obtained by dissolving γ-globulin (derived from human plasma; Fuji Film Wako Pure Chemical Industries, Ltd.) in water for injection (Otsuka Distilled Water; Otsuka Pharmaceutical Factory, Inc.) or 0.1 mol / L phosphate buffer solution (Fuji Film Wako Pure Chemical Industries, Ltd.) was added, and the flask was shaken at 20°C and 200 rpm for 1 hour in a bioshaker. The aqueous solution containing the adsorbent particles was then sucked up with a syringe and filtered through a 0.8 μm membrane filter. The protein concentration of the γ-globulin (derived from human plasma) solution was measured by the BCA method using a Protein Assay BCA Kit (Fujifilm Wako Pure Chemical Industries, Ltd.) (Te). In addition, a γ-globulin (derived from human plasma) solution before contact with the adsorbent was filtered through a 0.8 μm membrane filter, and the protein concentration was measured using a protein assay BCA kit (Ts). The protein adsorption rate was calculated according to the following formula. Protein adsorption rate (%) = [(Ts-Te) / Ts] x 100 In addition, the same procedure as above was carried out using the adsorbent of Example 1, 3, 6, 7, or 8, except that various proteins shown in Table 2 were used in addition to γ-globulin, to determine the protein adsorption rate.

[0071] (2-4) Analysis of average pore size The cationized silica gel particles of Examples 1 to 13 and Comparative Examples 1 to 3, and the activated carbon particles of Comparative Example 4 were pretreated for 3 hours in a vacuum at 100° C. Nitrogen gas adsorption analysis was carried out using BELSORP-max under conditions of a saturated vapor pressure of 101.33 kPa and an adsorption temperature of 77,000 K, and the average pore diameter was calculated by the Barrett-Joyner-Halenda method (BJH method).

[0072] The results are shown in Tables 1 and 2. The particle sizes in Table 1 are values ​​measured by the sieving method described below. The base material was placed on the top sieve of a standard sieve (stacked from top to bottom in the order of mesh sizes 25μm, 32μm, 40μm, 63μm, 75μm, 100μm, 125μm, 150μm, 200μm, 300μm, 425μm, and bottom container) specified in JIS Z8801, and sieved by vibrating for 10 minutes, after which the particle weight at each stage was measured. The mesh size through which the particles could not pass was taken as the minimum particle size, and the maximum mesh size at which 1% or more of the total particles were present was taken as the maximum particle size. The average pore diameters in Table 1 are values ​​calculated by the method described in the section "(2-4) Analysis of average pore diameter." The molecular weights and isoelectric points in Table 2 are the values ​​listed in the catalog for the purchased proteins. [Table 1]

[0073] Comparing Examples 1 to 4 and 10, 11, and 13 with Comparative Examples 1 and 2, the ET adsorption rate is extremely high in all cases, but the protein adsorption rate is very high at pore sizes of 43 nm or more and decreases to a few percent at pore sizes of 23 nm or less. It is clear that the critical point for suppressing protein adsorption is between pore sizes of 43 nm and 23 nm.

[0074] Furthermore, even when the cationic group-donor compound was changed from DEAP to DDA, DMOA, TMPB, AP, or MAP, a very high ET adsorption rate and a very low protein adsorption rate were similarly achieved (Comparison between Example 1 and Examples 5 to 9 and 12). The structural formulae of DEAP, DDA, DMOA, TMPB, AP, and MAP are shown below. [ka] [ka] [ka] [ka] [ka] [ka] These cationic group-donating compounds have different amine series after binding to the substrate, and different types and lengths of carbon chains bound to the nitrogen atoms, giving rise to significantly different cationic groups. It can be seen that, regardless of the type of cationic group containing a nitrogen atom, ET adsorption and inhibition of protein adsorption are compatible when the average pore size is 40 nm or less.

[0075] [Table 2] As shown in Table 2, the ET adsorbent of the present invention, which has an average pore diameter of 40 nm or less, adsorbs ET extremely efficiently while suppressing the adsorption of a wide range of proteins with various molecular weights and isoelectric points. [Industrial Applicability]

[0076] The ET adsorbent of the present invention has a very high ET adsorption capacity and hardly adsorbs proteins, and is therefore useful for removing ET from protein solutions or suspensions. In addition, since the base material is an inorganic material, it can be suitably used for medical applications requiring high-temperature sterilization.

Claims

1. An endotoxin adsorbent comprising an inorganic substrate having a cationic group containing a nitrogen atom, and having no pores, or having pores, the pore size of which is 40 nm or less.

2. The endotoxin adsorbent according to claim 1 , wherein the inorganic substrate is a silica substrate.

3. 3. The endotoxin adsorbent according to claim 1 or 2, wherein the cationic group containing a nitrogen atom is bound to the inorganic substrate with or without a spacer.

4. The endotoxin adsorbent according to claim 3, wherein the cationic group containing a nitrogen atom is bonded to the inorganic substrate via a spacer, and the spacer is a molecular chain having an epoxy group, an isocyanate group, or a hydroxyl group and a functional group capable of reacting with a functional group possessed by the inorganic substrate, or a compound which generates these functional groups by ring-opening.

5. The endotoxin adsorbent according to claim 1 or 2, which is in a particulate form and has an average particle size of 1 to 1000 μm.

6. A column for removing endotoxin, comprising a column packed with the endotoxin adsorbent according to claim 1 or 2.

7. 3. A method for producing a liquid containing proteins and from which endotoxins have been removed, comprising the step of contacting a liquid to be treated, which contains proteins and endotoxins, with the endotoxin adsorbent according to claim 1 or 2.

Citation Information

Patent Citations

  • Pyrogen adsorbent

    JP1992256434A

  • Endotoxin adsorbent

    WO2017018524A1